2014
DOI: 10.1111/lcrp.12047
|View full text |Cite
|
Sign up to set email alerts
|

Schema modes in criminal and violent behaviour of forensic cluster B PD patients: A retrospective and prospective study

Abstract: Purpose A clear understanding of an offender's criminal behaviour is a prerequisite for determining suitable treatment. In the literature, several specific frameworks or therapeutic approaches that aim to explicate criminal behaviour can be distinguished (e.g., cognitive analytic therapy, offence paralleling behaviour paradigm), but Schema Therapy (ST) is becoming an increasingly popular paradigm. According to forensic ST's theoretical framework, criminal and violent behaviour can be explained by an unfolding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 86 publications
6
43
0
4
Order By: Relevance
“…As very little is known about situational triggers of dark triad states at work, we can anticipate results only based on research on influencing factors of dark triad traits (Jonason et al, 2016) and maladaptive behaviors that are clinically relevant (i.e., schema modes; Keulen-de Vos et al, 2014). Research suggests for example that antisocial behavior at work (Robinson and O’Leary-Kelly, 1998; Lubit, 2002), competitive environments (Greenberg, 1990) and environments that can reduce a sense of behavioral accountability (e.g., cyberspace; Nevin, 2015) could facilitate dark personality expressions at work via social learning processes.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…As very little is known about situational triggers of dark triad states at work, we can anticipate results only based on research on influencing factors of dark triad traits (Jonason et al, 2016) and maladaptive behaviors that are clinically relevant (i.e., schema modes; Keulen-de Vos et al, 2014). Research suggests for example that antisocial behavior at work (Robinson and O’Leary-Kelly, 1998; Lubit, 2002), competitive environments (Greenberg, 1990) and environments that can reduce a sense of behavioral accountability (e.g., cyberspace; Nevin, 2015) could facilitate dark personality expressions at work via social learning processes.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…They found that borderline patients with PD were characterized by the aforementioned schema mode model. Keulen-de Vos, Bernstein, and Duggan (2016), Keulen-de Vos, Bernstein, Vanstipelen, et al (2016), and Keulen-de Vos, van den Broek, Bernstein, Valentin, and Arntz (2016) recently showed that vulnerable emotions seem to be involved in triggering criminal behaviour and institutional transgressions in forensic patients with cluster-B personality disorders. Descriptions of patients' crimes and the events leading up to the crime were rated for schema modes in a sample of 95 hospitalized cluster-B PD offenders.…”
Section: Schema Modesmentioning
confidence: 99%
“…In this study, we followed up on Keulen-de Vos, , Keulen-de Vos, Bernstein, Vanstipelen, et al (2016), and Keulen-de Vos, van den Broek, et al (2016) and further tested the construct validity of the schema mode concept. According to ST's theoretical framework, criminal and violent behaviour can be explicated by the unfolding sequence of schema modes.…”
Section: Present Study and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations